Transcriptomic profiling of the mussel Mytilus trossulus with a special emphasis on integrin-like genes during development. Issue 4 (2nd October 2019) - Maiorova, Mariia A.; Satoh, Noriyuki; Khalturin, Konstantin; Odintsova, Nelly A.
ABSTRACT: This study is based on the Illumina RNA-sequencing data obtained for a de novo assembly of the transcriptome from early developmental stages and some tissues and cells of the adult mussel Mytilus trossulus (Mytilidae, Mollusca) using the Trinity program. A total of 200, 079 contigs were obtained, and compared to the NCBI database using BLAST to search for sequence similarity. The number of annotated contigs under the GO term 3 categories was estimated to reach 19.96%. The BUSCO analysis determined a level of 99.2% completeness for the assembled transcriptome. The main findings include evidence that the mussel β integrin-like protein sequences are very similar to the β integrin-like proteins so far sequenced for all classes of Mollusca, while the highest similarity is observed between mussel and oyster ( Crasostrea gigas ) β integrin-like proteins. Our transcriptome dataset contributes to the genetic databases of non-model animals such as bivalves and represents the first characterization of expressed sequences during early development of the mollusc M. trossulus from the Sea of Japan including the identification of candidate genes involved in cell adhesion.